A (im)penhorabilidade das reservas financeiras contidas nos planos de previdência privada - Agostinho, Theodoro Vicente (2021)
The scope of this thesis is to discuss the private pension plans in Brazil and the controversy surrounding the legality of the pledge of funds for debt settlement purposes, especially tax, in view of the predictability in an ordinance regulated by the Attorney General of the National Treasury (Ordinance nº 396/2016) which consists of the set of measures, administrative or judicial, aimed at optimizing the processes related to the collection of the Federal Government's Debt, observing the criteria of economy and rationality, senior granting greater efficiency to the recovery of registered credit, among them a pledge on supplementary pension proceeds. It is noteworthy that private pension, also called supplementary pension, is a way of guaranteeing future income to the holder or beneficiary, generally defined after the retirement period, being used as extra income and ensuring better social interaction and dignified aging. The Complementary Pension Scheme is voluntary in nature, being autonomously organized without a social security scheme and intended for the formation of reserves for the payment of pension benefits, being systematized into two aspects: open and closed. Having a vast importance not only for the country's economy in the face of the taxation involved, that is, a tax on income tax, but also presented for the life of each insured, given the space between real protection and the protection necessary for maintenance income and standard of living of the beneficiary. It happens that after the understanding signed by the Superior Court of Justice (STJ), in which the amounts deposited in private pension plans do not have a food nature, thus acquiring the character of savings or investment, the reason why they can be pledged. Several requests for attachment were raised in court, especially the action of the Attorney General of the National Treasury (PGFN), intensifying the attachment of tax debts. However, there is a dispute over the illegality of the attachment will be applicable and the nature of the private supplementary pension, mainly due to the fact that the Civil Procedure Code lists retirement, annuity and pensions as unseizable, a subject that is addressed in this work